Pengaruh Amonia, Karbondioksida dan Debu pada Ayam Broiler Pada Pemeliharaan dengan Suhu Ruang Berbeda: The Effect of Ammonia, Carbon Dioxide, and Dust of Broilers Farming with Different Room Temperature - Asma'ul Fitriana Nurhidayah; Niken Ulupi; Salundik; St Chadijah; Hasrin; Abdul Alim Yamin (Anoa: Journal of Animal Husbandry, 2022)
This study aims to study the impact on Maintenance broilers of temperature differences on ammonia, carbon dioxide, and dust. The completely randomized design (CRD) was used for the experiment design, with temperature of 20oC (KS20) and 30oC (KS30) as treatments. The experiment was repeated four times and each replication contained of 10 chickens. The ammonia, carbon dioxide, and dust sample was taken three times, at the 3rd, 4th, and 5th week of the experiment. Ammonia concentration during the 4th week was 0.08 ppm and increased to 2.022 -2.027 ppm at the 5th week; the carbon dioxide concentration at low temperature and high temperature was increased 17.76-22.13 ppm at the 5th week. The total dust increased at the 5th on the low temperature condition. The conclusion of this study, broilers were maintained at high temperature (30oC) produced lower air quality, in conditions this indicate that the broilers environment with conditions reared at high temperatures is still in a good condition.